Ryanodine receptor phosphorylation by CaMKII promotes spontaneous Ca2+ release events in a rodent model of early stage diabetes: The arrhythmogenic substrate - Sommese, Leandro Matías (2016)
Background: Heart failure and arrhythmias occur more frequently in patients with type 2 diabetes (T2DM) than in the general population. T2DM is preceded by a prediabetic condition marked by elevated reactive oxygen species (ROS) and subclinical cardiovascular defects. Although multifunctional Ca2+ calmodulin-dependent protein kinase II (CaMKII) is ROS-activated and CaMKII hyperactivity promotes cardiac diseases, a link between prediabetes and CaMKII in the heart is unprecedented. Objectives: To prove the hypothesis that increased ROS and CaMKII activity contribute to heart failure and arrhythmogenic mechanisms in early stage diabetes. Methods–Results: Echocardiography, electrocardiography, biochemical and intracellular Ca2+ (Ca2+i) determinations were performed in fructose-rich diet-induced impaired glucose tolerance, a prediabetes model, in rodents. Fructose-rich diet rats showed decreased contractility and hypertrophy associated with increased CaMKII activity, ROS production, oxidized CaMKII and enhanced CaMKII-dependent ryanodine receptor (RyR2) phosphorylation compared to rats fed with control diet. Isolated cardiomyocytes from fructose-rich diet showed increased spontaneous Ca2+i release events associated with spontaneous contractions, which were prevented by KN-93, a CaMKII inhibitor, or addition of Tempol, a ROS scavenger, to the diet. Moreover, fructose-rich diet myocytes showed increased diastolic Ca2+ during the burst of spontaneous Ca2+i release events. Mice treated with Tempol or with sarcoplasmic reticulum-targeted CaMKII-inhibition by transgenic expression of the CaMKII inhibitory peptide AIP, were protected from fructose-rich diet-induced spontaneous Ca2+i release events, spontaneous contractions and arrhythmogenesis in vivo, despite ROS increases. Conclusions: RyR2 phosphorylation by ROS-activated CaMKII, contributes to impaired glucose tolerance-induced arrhythmogenic mechanisms, suggesting that CaMKII inhibition could prevent prediabetic cardiovascular complications and/or evolution.